(untitled) (Health and Biosciences, 2020)
Several procedures have been used to Fibro edema gelloid (FEG) treatment this dysfunction, including radiofrequency and endermology. The present study aimed to analyze radiofrequency procedures and endermology in the treatment of FEG. The research was carried out on 9 women (FEG grades I and III), aged between 20 and 40 years. Radiofrequency was used with 85% intensity and 2.4 Mhz frequency, at 38ºC temperature. The endermology was used at 200mmHG pressure until it caused local hyperemia. The session lasted 50 minutes. The parameters used in the evaluation were: thermography, level of patient question satisfaction, images of the buttocks through photographs, and perimetry. The evaluations took place on the first day and after eight treatment sessions in the hip and gluteal fold regions. For data analysis, the paired T-student test was used. At the initial physical examination, all patients presented FEG in the gluteal region (thermography and visual), concerning perimetry, before and after the treatment, a difference (p <0.05) was observed in the hip region after treatment, however, there was no difference in the gluteal fold region (p> 0.05). All subjects reported an improvement in tonicity and in the appearance of the FEG, which can be observed through the photos. Through the results obtained in this study, the radiofrequency protocol associated with endermology proved to be an effective adjunct measure in the treatment of FEG, proving to be effective in easing the condition of EGF, and satisfaction concerning to the proposed treatment and the aspect of EGF after treatment.